Edukasi Legalitas Kosmetik dan BPOM Mobile Pada Siswa SMA Negeri 2 Ungaran - Erwiyani, Agitya Resti; Ari Siswati; Istianatus Sunnah (UNIVERSITAS NGUDI WALUYO, 2024)
The use of cosmetics has become a necessity and lifestyle, especially for teenagers who often try various types of cosmetics. The use of cosmetics by teenagers is intended to maintain healthy facial skin, increase self-confidence, overcome acne and follow trends in society or their idols. Cosmetic purchases by teenagers are often made based on information obtained from social media, reviews from friends or communities, internet sources or television. Online purchases in the marketplace are often influenced by reviews from previous cosmetic buyers, but reviews from buyers do not necessarily guarantee the truth of the information provided. The aim of educational activities for students of SMA Negeri 2 Ungaran is to increase students' knowledge on how to identify the authenticity of cosmetics and how to find information on prohibited cosmetics. The activity was carried out with the target participants of SMA Negeri 2 Ungaran class X students as many as 13 male students and 18 female students. Educational activities were carried out through presentations, discussions and questions and answers. The level of student understanding was measured using post-test questions that were done after the presentation of material from the resource person. The results of measuring the level of student understanding about the legality of cosmetics and BPOM mobile had a good level of knowledge of 67.75%, moderate at 25.81% and lacking at 6.45%. It is necessary to carry out educational activities for adolescents with a wider scope. ABSTRAK Penggunaan kosmetik telah menjadi kebutuhan dan gaya hidup terutama remaja yang sering mencoba berbagai jenis kosmetik. Penggunaan kosmetik pada remaja ditujukan untuk menjaga kesehatan kulit wajah, meningkatkan rasa percaya diri, mengatasi jerawat serta mengikuti tren di masyarakat ataupun idola mereka. Pembelian kosmetik pada remaja seringkali dilakukan berdasarkan informasi yang didapatkan dari media sosial, review dari teman atau komunitas, sumber internet maupun televisi. Pada pembelian secara online di market place seringkali dipengaruhi oleh review dari pembeli kosmetik sebelumnya namun review dari pembeli belum tentu menjamin kebenaran informasi yang diberikan. Tujuan kegiatan edukasi di siswa SMA Negeri 2 Ungaran untuk meningkatkan pengetahuan siswa bagaimana melakukan identifikasi keaslian kosmetik serta mengetahui bagaimana cara mencari informasi kosmetik yang dilarang. Kegiatan dilakukan dengan sasaran peserta siswa SMA Negeri 2 Ungaran kelas X sebanyak 13 siswa laki – laki dan 18 siswa perempuan. Kegiatan edukasi dilakukan dengan presentasi, diskusi dan tanya jawab. Tingkat pemahaman siswa diukur menggunakan soal post test yang dikerjakan setelah pemaparan materi dari narasumber. Hasil pengukuran tingkat pemahaman siswa tentang legalitas kosmetik dan BPOM mobile memiliki tingkat pengetahuan baik sebesar 67,75%, sedang sebesar 25,81% dan kurang sebesar 6,45%. Perlu dilakukan kegiatan edukasi pada remaja dengan lingkup yang lebih luas.